2007
DOI: 10.1063/1.2768306
|View full text |Cite
|
Sign up to set email alerts
|

Central peak and acoustic anomalies of the relaxor ferroelectric lead magnesium niobate-lead titanate single crystal studied by the micro-Brillouin scattering

Abstract: Quasielastic central peak and acoustic anomalies in a [001] lead magnesium niobate-lead titanate single crystal have been investigated by the high-resolution micro-Brillouin scattering. Two acoustic anomalies were observed at temperatures, TC-T∼415K and TT-R∼348K. The damping showed a significant dispersion at T∼550K, associated with the enhanced dynamics of local strain fields created by the polar microregions. The temperature evolution of the quasielastic central peak exhibited anomalies in the overall inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…In fact the appearance of narrow CP in PMN-PT system well below T B could be taken as the evidence for the existence of T ‫ء‬ . 14 In the present study also, the appearance of narrow CP and the coupling of the broad CP with LA phonon mode below T ‫ء‬ indeed support the existence of T ‫ء‬ where the longlived PNRs begin to form. The existence of T ‫ء‬ has also been established in another class of relaxor ferroelectric systems such as PST and PBST through Raman spectroscopic studies.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…In fact the appearance of narrow CP in PMN-PT system well below T B could be taken as the evidence for the existence of T ‫ء‬ . 14 In the present study also, the appearance of narrow CP and the coupling of the broad CP with LA phonon mode below T ‫ء‬ indeed support the existence of T ‫ء‬ where the longlived PNRs begin to form. The existence of T ‫ء‬ has also been established in another class of relaxor ferroelectric systems such as PST and PBST through Raman spectroscopic studies.…”
supporting
confidence: 58%
“…21 The dielectric studies on the composition near MPB show cubic-tetragonal ͑T ct ͒ and tetragonal-rhombohedral ͑T tr ͒ phase transitions that are similar to PMN-PT and PZN-PT systems. 14,22 However unlike PMN-PT and PZN-PT systems, the studies on the dynamical aspects of PNRs have not yet been carried out in PIN-PT solid solution system. Such studies on broader compositional system will help in the better understanding on the various physical aspects of PNRs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Extensive studies on the dynamical aspects of PNRs have been carried out in prototype RFEs such as Pb(Mg 1/3 Nb 2/3 )O 3 (PMN) and other related systems through neutron and light scattering studies. [3][4][5][6][7][8][9] Brillouin scattering studies in these systems directly revealed the dynamical features of the PNRs such as the slowing down of their relaxation time and the coupling between the polarization fluctuations and acoustic phonon modes through the appearance of central peak (CP) and softening of the acoustic phonon mode. [6][7][8][9] This paper focuses on micro-Brillouin scattering studies on the dynamical aspects of PNRs in partially ordered Pb(Sc 1/2 Ta 1/2 )O 3 (PST) without any Pb vacancies.…”
Section: Introductionmentioning
confidence: 99%